EVALUATION OF PROXIMATE, PHYTOCHEMICAL AND MINERAL COMPOSITIONS OF LEAF, STEM AND ROOT OF BRYOPHYLLUM PINNATUM AND PHYLLANTHUS AMARUS - U, Olayinka B.; O, Babatunde M.; O, Ogundare G.; V, Kayode O.; H, Muhammad T.; G, Daramola G.; F, Bulala A.; A, Abdulbaki S. (Science Journal of University of Zakho, 2024)
Bryophyllum pinnatum and Phyllanthus amarus are plants that have been established to contain bioactive substances for various therapeutic advantages, most importantly their leaves. Information on the other parts of the plant, such as stem and root, is scanty in literature; hence, there is a need to compare the various parts of the plants in terms of proximate composition, phytochemicals, and mineral elements. The results showed that the two plants had the highest amount of carbohydrate (62.09 - 63.98%) and followed in decreasing order of magnitude by protein (16.04 - 17.50%), moisture (10.05 - 10.35%), fibre (3.9 - 4.36%) and ash (3.80 - 4.03%). The fat contents in both plants ranged from 1.09% to 2.03% in Phyllanthus amarus and Bryophyylum pinnate leaves, respectively. Alkaloids (106.97 - 108.46 mg/100g) were highest in all the plants, while steroids (0.11 - 0.17 mg/100g) were lowest. Generally, in both plant parts, the leaf and stem had a higher amount of the foregoing proximate and phytochemicals when compared to the root. Considering the macronutrients, all the plant parts contained the highest amount of potassium (29.04 - 30.03 mg/100g) and the lowest amount of nitrogen (0.25 - 0.27%). Iron (26.3 - 27.7 mg/100g) was the highest among the micronutrients, while copper was the lowest (0.70 - 0.73 mg/100g). The study concluded that both plants showed proximate phytochemicals and mineral nutrients that were unevenly distributed in the various parts of the plant, with the leaf and stem exhibiting higher concentrations compared to the root. Therefore, adequate knowledge of the distribution of these chemical constituents will provide a baseline for the selection of parts to be used for health benefits.
Keywords: Proximate; phytochemical; mineral composition; Phyllanthus amarus; Bryophyylum pinnatum